Towards an integrated framework of e-learning through an international innovative collaboration: Iraqi perspective - Mahmod, Mohamed Ali; Md Ali, Asma; Ahlan, Abdul Rahman; Shah, Asadullah; Abu Seman, Muhamad Sadry (Institute of Electrical and Electronics Engineers Inc., 2018)
Electronic Learning (e-learning) is the process of offering education in a creative method by using the electronic shapes of information and contents. e-learning is the process of education that offered can be divided into online or distance education, which means that it can deliver education to everyone around the world online through the electronic means such as the internet from different distant countries. The success of E-learning process in universities needs to some factors that should be fit with the revolution of technology and enhance the learner's knowledge. Universities in developing countries such as Iraq, in order to be fit with the rapid growth of technology, it needs to collaborate with other national and international universities to develop e-learning tools and methods. In order to contribute to the success of the e-learning process in universities in Iraq, these universities have to adopt collaboration culture with other universities and adhocracy culture to follow the innovation in e-learning process. This paper proposes an integrated model of e-learning through an innovative collaboration environment which could participate to improve and add values to the e-learning process in universities in Iraq.